The Relationship Between Midwives' Knowledge and Attitudes Toward The Provision of Acupressure to Reduce Pain During Labor - Fitria, Henni; Yulizawati, Yulizawati; Bradinda, Sisca; Mardiyah, Radhiyatan (Universitas Andalas, 2023)
Myometrial contractions, which cause labor pain, are a physiological process that varies in intensity depending on the individual. Most women who go through labor feel pain, but not all of them deal with it well. Anxiety and irregular labor might result from improper management of labor pain. It is possible to lessen labor pain by using both pharmaceutical and non-pharmacological interventions. In order to prepare moms and lower maternal anxiety during labor, non-pharmacological therapies like acupressure are thought to lessen the severity of labor pain. From August to October 2023, research using a cross-sectional study design was carried out at the Independent Midwife Practice in Padang City. Up to 40 midwives who worked or had their own independent midwifery practice in Padang City made up the research sample. Systematic random sampling was used to collect the samples. Chi square analysis test (pâ‰¤0.05) was used for both univariate and bivariate data analysis. The findings demonstrated that 47.5% of respondents had strong knowledge, and 72.5% had a positive attitude. The bivariate test results, with p values of 0.018 and 0.044, indicated a link between respondents' knowledge and attitude toward the supply of acupressure. When it comes to the providing of labor acupressure, knowledge and attitude are significantly correlated.